Efficacy and safety of venetoclax combined with hypomethylating agents for relapse of acute myeloid leukemia and myelodysplastic syndrome post allogeneic hematopoietic stem cell transplantation: a systematic review and meta-analysis - Yufeng Du; Chunhong Li; Zhijia Zhao; Yikun Liu; Chengtao Zhang; Jinsong Yan (BMC Cancer, 2023)
Abstract Background Currently, there is no standard treatment for managing relapse in patients with acute myeloid leukemia and myelodysplastic syndrome (AML/MDS) after allogeneic hematopoietic cell transplantation. Venetoclax-based therapies have been increasingly used for treating post-transplantation relapse of AML. The aim of this systematic review and meta-analysis was to evaluate the efficacy and adverse events of Venetoclax combined with hypomethylating agents (HMAs) for AML/MDS relapse post-transplantation. Methods We searched PubMed, Web of Science, Excerpta Medica Database, Cochrane Library, and Clinical. gov for eligible studies from the inception to February 2022. The Methodological Index for Non-Randomized Studies was used to evaluate the quality of the included literatures. The inverse variance method calculated the pooled proportion and 95% confidence interval (CI). Results This meta-analysis included 10 studies involving a total of 243 patients. The pooled complete response and complete response with incomplete blood count recovery rate of Venetoclax combined with HMAs for post-transplantation relapse in AML/MDS was 32% (95% CI, 26-39%, I2 = 0%), with an overall response rate of 48% (95% CI, 39-56%, I2 = 37%). The 6-month survival rate was 42% (95% CI, 29-55%, I2 = 62%) and the 1-year survival rate was 23% (95% CI, 11-38%, I2 = 78%). Conclusion This study demonstrated a moderate benefit of Venetoclax in combination with HMAs for patients with relapsed AML/MDS post-transplantation (including those who have received prior HMAs therapy), and may become one of treatment options in the future. Large-scale prospective studies are needed to confirm the potential benefit from venetoclax combined with HMAs.